2022
DOI: 10.1038/s42003-022-04277-w
|View full text |Cite
|
Sign up to set email alerts
|

Half-millennium evidence suggests that extinction debts of global vertebrates started in the Second Industrial Revolution

Abstract: Extinction debt describes the time-lagged process of species extinction, which usually requires dozens to hundreds of years to be paid off. However, due to the lack of long-term habitat data, it is indeterminate how strong the signal of extinction debts is at the global scale and when the debts started. Here, by compiling the geographical distributions of 6120 reptiles, 6047 amphibians, and 4278 mammals and correlating them with annual forest cover data from 1500 to 1992, we show that the beginning of the Seco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…This finding suggests that minimizing deforestation at the equator via the creation and maintenance of protected areas may have disproportionately beneficial impacts on forest species conservation (Anjos et al., 2019; Sverdrup‐Thygeson et al., 2017; Vargas‐Cárdenas et al., 2022). Additionally, our results suggest that reforesting historically deforested areas is a conservation priority since they contain disproportionately high proportions of forest species, which may be declining towards local extinction (Liao et al., 2022; Tilman et al., 1994). Ultimately, we report a striking relationship between the proportion of forest species and latitude, which can only partially be explained by the variables we investigated in this study, such as current and historical forest cover, forest structure and temporal stability, disturbance regimes, altitude, and total species richness.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…This finding suggests that minimizing deforestation at the equator via the creation and maintenance of protected areas may have disproportionately beneficial impacts on forest species conservation (Anjos et al., 2019; Sverdrup‐Thygeson et al., 2017; Vargas‐Cárdenas et al., 2022). Additionally, our results suggest that reforesting historically deforested areas is a conservation priority since they contain disproportionately high proportions of forest species, which may be declining towards local extinction (Liao et al., 2022; Tilman et al., 1994). Ultimately, we report a striking relationship between the proportion of forest species and latitude, which can only partially be explained by the variables we investigated in this study, such as current and historical forest cover, forest structure and temporal stability, disturbance regimes, altitude, and total species richness.…”
Section: Discussionmentioning
confidence: 81%
“…This suggests that forest species which occurred in the area before deforestation still at least partially remain; likely in smaller forest remnants. Whether the high proportions of forest species in such areas will remain long‐term is unknown, however, previous studies have found lagged responses of species to habitat loss (Chen & Peng, 2017; Liao et al., 2022; Tilman et al., 1994), which only increase as the size of the area increases (Haddad et al., 2015), meaning that this may be a case of extinction debts that are yet to be paid, and could take centuries to do so (Chen & Peng, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation